Development and Characterization of a Baked Snack from Rings of Green Apples - Tavera Quiroz, Maria Jose (2014)
Apple snacks were developed from green apple (Granny Smith) by baking. The effect of several pretreatments on properties such as color, texture, moisture, and water activity was studied. Blanching with steam, impregnation with calcium salts (calcium carbonate/calcium lactate), impregnation with sugars (fructose and maltodextrin), and addition of ascorbic acid were some of the pretreatments used. The addition of calcium proved to be favorable since it caused a reduction in the porous structure of the apple tissue associated with a greater firmness. The optimum selection of pretreatments on the rings of green apples gave as a result a snack with a higher acceptability in the evaluated attributes (color, sour taste, sweetness, and texture). Irrespective of the composition of the used solution of sugars, moisture, water activity, and lightness (L) of the baked apple rings did not differ significantly. The antioxidant activity of the obtained snack increased compared to that of fresh fruit due to the addition of ascorbic acid. The ascorbic acid content of apple snacks also turned out to be higher than that of fresh apples.